ANTONIM DALAM BAHASA DAYAK RIBUN - Amanah Hijriah (Balai Bahasa Kalimantan Barat, 2020)
Ribun language is one of the languages found in Sanggau district, West Kalimantan. This paper examines antonyms in Ribun language. Antonyms is one of the semantic studies. The problem in this study includes how the form of antonyms contained in Ribun language. The aim to be achieved is to describe the form of antonyms in Ribun Language. Data collection used the method of listening to involved with interviews, notes and recordings. Data in the form of oral speech from the Ribun community in Kedakas Village, TayanHulu District, Sanggau Regency, West Kalimantan Province. Data collection time was from February 2018 to April 2018. Furthermore, recording and documenting data in the form of notes used to collect data. After being collected, language data were analyzed using the aggregate method. Then, the results of the analysis of the language data were presented with informal and formal methods. There are antonym words in Ribun language which include adjectives, verbs and nouns.